Education of natural science in schools with help of experiments of food investigations - Izsák Margit (Élelmiszervizsgálati közlemények, 2016)
Experiments play a particularly important role in the teaching of science subjects. Students are very fond of experiments performed with substances well-known to them, in our case, foods. In this article, ten simple physical, chemical and biological experiments are described in the following topics: microwave heating for mass and water content determination, discoloring a tea beverage, unscrewing the top of a jam bottle, changes in the texture of biscuits and bread during storage, dissolution and chemical reactions of cooking oil, thermal instability of margarine, determination of the acid degree value of milk, hydrolysis of egg protein, and protein denaturation. Foods used in the tests and experiments are: ascorbic acid, lemons, citric acid, jam, cooking oil, fruit juice, fruit syrup, traditional tea, fruit tea, biscuits, bread, margarine, baking soda, milk and egg protein. The experiments were designed at Congregatio Jesu Ward Maria Elementary School, High School and Music Vocational School of Budapest, where the scientific, ethical and human education are on equaled level.